2016
DOI: 10.3389/fphar.2016.00327
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of ErbB Activating Events and Signal Transduction on Antigen Processing and Presentation: MHC Expression as a Model

Abstract: Advances in molecular pathology have changed the landscape of oncology. The ability to interrogate tissue samples for oncogene amplification, driver mutations, and other molecular alterations provides clinicians with an enormous level of detail about their patient’s cancer. In some cases, this information informs treatment decisions, especially those related to targeted anti-cancer therapies. However, in terms of immune-based therapies, it is less clear how to use such information. Likewise, despite studies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 212 publications
(185 reference statements)
1
8
0
Order By: Relevance
“…For example, oral administration of amoxicillin, cefotaxime, and vancomycin decreased the abundance and altered the gut microbiota composition in rats[ 17 ]. The gut microbiota diversity indicated by the Shannon index was lower in both the antibiotic groups than in the control group, suggesting that the antibiotics reduced not only the richness but also the diversity of the gut microbiota, which is in line with results from previous studies[ 17 , 36 ]. Our study also found that azithromycin decreased the relative abundance of Bacteroidetes and Proteobacteria and increased the relative abundance of Firmicutes , which corresponds with the results of most other studies [ 6 , 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…For example, oral administration of amoxicillin, cefotaxime, and vancomycin decreased the abundance and altered the gut microbiota composition in rats[ 17 ]. The gut microbiota diversity indicated by the Shannon index was lower in both the antibiotic groups than in the control group, suggesting that the antibiotics reduced not only the richness but also the diversity of the gut microbiota, which is in line with results from previous studies[ 17 , 36 ]. Our study also found that azithromycin decreased the relative abundance of Bacteroidetes and Proteobacteria and increased the relative abundance of Firmicutes , which corresponds with the results of most other studies [ 6 , 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…The literature supports the ability of oncogene-driven pathways to negatively influence immunological function such that oncogene-targeted agents unleash an IFN response arising within the tumor cells [ 16 , 26 , 27 , 52 ]. While our study focused on chemokines and cytokines regulated in response to EGFR/ERBB inhibition in HNSCC cells, Pollack et al showed that EGFR inhibition can augment expression of CIITA and antigen presenting machinery (APC) [ 19 , 20 ]. In support, our human HNSCC cell lines also showed induction of MHC class I (B2M) and MHC class II (HLA-DM) genes in response to ERBB inhibition (Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to agents that directly target host immunity, it is becoming clear that both cytotoxic and oncogene-targeted agents can induce mobilization of immune cells that are postulated to contribute both positively and negatively to the therapeutic response in HNSCC and other solid tumors [ 16 – 18 ]. The literature also demonstrates the ability of EGFR inhibitors to increase MHC expression and antigen presentation on tumor cells [ 19 21 ]. In fact, the ability of EGFR and MAPK pathway inhibitors to induce genes involved in antigen presentation likely reflects the activation of a larger interferon transcriptional program that, in addition to antigen presentation, includes a host of chemokines, cytokines and antiviral genes [ 22 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to optimally design these clinical trials, it is critical to understand how EGFRIs influence the expression of genes coding for immune regulators, especially those that govern the interaction between tumors and T cells (for example, HLA class I molecules). In the last 10 years, many groups have explored the influence of anti-EGFR agents on HLA class I expression in tumors and found that TKIs (such as PD168393, AG1478 and gefinitib), as well as the antibody cetuximab, enhance HLA class I expression ( Kersh et al, 2016 ). Our current results showed that nimotuzumab also increases the tumor surface expression of HLA class I molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that EGFR-specific CD8 + T cells may contribute to clinical response in cancer patients treated with anti-EGFR mAbs ( Srivastava et al, 2013 ). In addition, some mAbs and TKIs now used in patients have been validated as positive regulators of the tumor expression of HLA class I and antigen processing machinery (APM) components ( Kersh et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%